-4(8x+7x)=-10-6x

Simple and best practice solution for -4(8x+7x)=-10-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(8x+7x)=-10-6x equation:



-4(8x+7x)=-10-6x
We move all terms to the left:
-4(8x+7x)-(-10-6x)=0
We add all the numbers together, and all the variables
-4(+15x)-(-6x-10)=0
We multiply parentheses
-60x-(-6x-10)=0
We get rid of parentheses
-60x+6x+10=0
We add all the numbers together, and all the variables
-54x+10=0
We move all terms containing x to the left, all other terms to the right
-54x=-10
x=-10/-54
x=5/27

See similar equations:

| 10(x+3=-20 | | 5x-6=28 | | 5=3-1/2x | | 9y-11.4=4.8 | | 14-7x=14+35x | | 1/2x-39.15=38.50 | | -16-6x=-6(x+3 | | 3(b-1)=3b-1+b | | -1.14-11.1s=-11s | | -8+x+15=23 | | 7/16=z/8 | | 2x+2x=2=4x+2 | | (D+3)(D+4)y=0 | | -5x-9x=-6(x+7)-11(-12-2x) | | 4(r+20)=1/5(20r+40) | | 5=2x+5/7=7 | | 6x-9x-10=-3x+9-10 | | -4(3x-2)=-24 | | 5x+4=9x-48 | | 3n+2=3(n-5) | | 3+2x-(x+1=3x-6 | | 4(x–1)–2(3x+5)=–3x+1 | | 2.7+1.9x=2x-1.5 | | -1(2m-1)=3 | | 3x+5+3x+17=3x+7+3x | | -(8-12k)=-2(8k-4) | | 11(r-3)=77 | | 3x+5+5x=-1 | | 5=4/2x | | 0.5t=3.6=4.2-1.5t | | 11-2(8+3p)=41 | | 5b=4/5 |

Equations solver categories